Effect of Microbial Cell-Size on Solid State Fermentation of Cowpea (Vigna unguiculata L. Walp) and Groundnut (Arachis hypogaea L.) by Rhizopus oligosporus - E. Aganbi; E. O. Egbune; O. C. Orororo; T. Ezedom; O. U. Egbune; N. J. Tonukari (Journal of Applied Sciences and Environmental Management, 2023)
The solid state fermentation of Vigna unguiculata L. Walp (cowpea) and Arachis hypogaea L. (groundnut) was carried out using Rhizopus oligosporus at different inoculum size (1.89 x 102, 3.78 x 102, 5.67 x 102, 7.56 x 102, 9.45 x 102 and 11.34 x 102 CFU g-1).  Following fermentation for 72 hours, biochemical parameters were determined in fermented and unfermented samples. All inoculum sizes produced significantly more phenol and flavonoids in the fermented groundnut samples as compared to the control, with the 15% inoculum size providing the most phenols (255.0 mg GAE/g). The fermentation of cowpea showed a similar pattern. The recognized antioxidant molecules flavonoids and phenols have sufficient capacity to reduce the negative effects of free radicals. The fermented samples' 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical increased significantly as compared to the unfermented sample. Comparing the fermented samples to the unfermented sample (control) at various inoculum sizes, amylase activity rose dramatically. Solid-state fermentation (SSF) can be employed to enhance the nutritional characteristics of cowpea and groundnut as soluble protein, glucose, and reducing sugars were also significantly increased in fermented cowpea and groundnut (at the different inoculum sizes) compared to the control. From this study, it is obvious that the selected fungus isolate, R. oligosporus showed high enzymatic activities and increased value added product of cowpea at varying inoculum size. This is an important characteristic for possible biotechnological applications.